Linguacultural Aspects of Studying the Russian Language in NonLanguage Faculties of Higher Educational Institutions - Babayeva Anjella Axatovna (Genius Journals, 2024)
The article analyzes and defines the study of culture in the educational process of students studying the Russian language at non-linguistic faculties of pedagogical higher educational institutions. The importance of studying foreign language culture by future teachers is shown. Linguistic and cultural material is described. Motivational factors of extracurricular educational activities of students are identified and some forms of this activity are described. cultural studies; Russian language; training based on virtual excursions; non-linguistic faculties; motivation; pedagogical condition
Keywords: Language; the linguocultural; communicative